Effects of Web-Based Parent Training on Caregiver Functioning Following Pediatric Traumatic Brain Injury: A Randomized Control Trial. Issue 6 (November 2018) - Raj, Stacey P.; Shultz, Emily L.; Zang, Huaiyu; Zhang, Nanhua; Kirkwood, Michael W.; Taylor, H. Gerry; Stancin, Terry; Yeates, Keith Owen; Wade, Shari L.
Abstract : Objective: To examine the effects of a Web-based parenting intervention (I-InTERACT), and an abbreviated version (Express), on caregiver depression, psychological distress, parenting stress, and parenting efficacy following pediatric traumatic brain injury (TBI). Setting: Four children's hospitals and 1 general hospital in the United States. Participants: 148 caregivers of 113 children aged 3 to 9 years with a moderate to severe TBI. Design: Multicenter randomized controlled trial. Participants were randomly assigned to I-InTERACT, Express, or an active control condition. Caregiver data were collected at baseline and postintervention (6 months later). Intervention: I-InTERACT (10-14 sessions) and Express (7 sessions) combine live coaching of parenting skills and positive parenting strategies. Main Measures: Center for Epidemiologic Studies Depression Scale (CES-D); Global Severity Index of the Symptom Checklist-90-R (GSI), Parenting Stress Index (PSI), and Caregiver Self-Efficacy Scale (CSES). Results: Analyses revealed no main effects of treatment on caregiver distress (GSI), parenting stress (PSI), or parenting efficacy (CSES). However, analyses examining baseline severity as a moderator found that caregivers with elevated levels of depression in I-InTERACT experienced significantly greater reductions in CES-D scores compared with caregivers in the active control condition. Conclusions: I-InTERACT reduced caregiver depression but no other facets of caregiver psychological functioning. Modifications to the treatment content may be necessary to reduce parenting stress and improve caregiver efficacy.